1998
DOI: 10.1046/j.1523-1747.1998.00108.x
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of Tumor Suppressor Protein Neurofibromin in Normal Human Wound Healing and In Vitro Evidence for Platelet Derived Growth Factor (PDGF) and Transforming Growth Factor-β1 (TGF-β1) Elicited Increase in Neurofibromin mRNA Steady-State Levels in Dermal Fibroblasts

Abstract: We first studied expression of neurofibromin by immunohistochemistry in scars obtained from operations involving areas of healing wounds. The results demonstrated increased immunoreactivity for neurofibromin in the fibroblastic cell population of the lesions when compared with fibroblasts of apparently healthy perilesional skin, or those of intact control skin. Furthermore, dermal fibroblasts of 19 and 34 wk-old fetuses displayed a clearly detectable immunosignal for neurofibromin. In vitro studies were design… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0
2

Year Published

2000
2000
2008
2008

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 43 publications
2
31
0
2
Order By: Relevance
“…It is known that neurofibromin directly impacts the Ras-signaling pathway, which interacts with multiple signaling pathways, several of which are important in bone. For example, transforming growth factor-beta increases neurofibromin mRNA (34), murine Nf1 Ϯ mast cells secrete elevated concentrations of transforming growth factor-beta (35), fibroblast growth factors activate the Ras/mitogen-activated phosphorylation kinase pathway (36), and inactivation of the SHP2-Ras-mitogen-activated phosphorylation kinase pathway in mice results in enhanced bone formation after an increase in osteoclast activity suggesting a dissociation of the intercellular communications between osteoclasts and osteoblasts (37,38). Specific investigations using the Nf1 haploinsufficient transgenic mouse model has shown abnormalities in myeloid cells.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that neurofibromin directly impacts the Ras-signaling pathway, which interacts with multiple signaling pathways, several of which are important in bone. For example, transforming growth factor-beta increases neurofibromin mRNA (34), murine Nf1 Ϯ mast cells secrete elevated concentrations of transforming growth factor-beta (35), fibroblast growth factors activate the Ras/mitogen-activated phosphorylation kinase pathway (36), and inactivation of the SHP2-Ras-mitogen-activated phosphorylation kinase pathway in mice results in enhanced bone formation after an increase in osteoclast activity suggesting a dissociation of the intercellular communications between osteoclasts and osteoblasts (37,38). Specific investigations using the Nf1 haploinsufficient transgenic mouse model has shown abnormalities in myeloid cells.…”
Section: Discussionmentioning
confidence: 99%
“…Neurofibromin is expressed in the skin (Malhotra & Ratner, 1994) and upregulated in fibroblasts after wounding (Yla-Outinen et al 1998). Excisional wounding demonstrated enlarged, deepened scar formation, as well as a pronounced increase in granulation tissue formation (even penetrating the underlying muscle), with a sustained fibroblast proliferation in vivo and in vitro (Atit et al 1999).…”
Section: Chemokinesmentioning
confidence: 99%
“…7,8 Interestingly, recent results demonstrate up-regulation of NF1 gene expression in response to tissue trauma and suggest that a "second hit" in a form of somatic mutations in lesional neurofibromatosis cells is not necessarily a prerequisite for the development of neurofibromas. 9 Atit et al 10 have shown that, in mice with NF1 mutations, injury promoted specific features of neurofibromas found in human patients,…”
Section: Commentmentioning
confidence: 99%